APLIKASI MONITORING KEAMANAN JARINGAN DENGAN MENGGUNAKAN IDS DAN ROUTER MIKROTIK - wiyanto, Pidie; Hamzah, Amir; Sholeh, Mohammad (Jurnal Jarkom, 2014)
ABSTRACTComputer network security system is an important thing in todayâs technological era. Security of data is vital point and need more extra control of it. Value of data within an institution or a particular company can be very valuable if the information contained in them can result in a gaining advantage of one or more parties. The system is capable to processingÂ  output data from mikrotik, and it can also recognize all activities an intruder in attempt to infiltrate into the system by usingÂ  port scanner, the ssh, ftp,then do the bloking of ip address that are considered as intruder after that the system will provide a report to the administrator through webserver of the presence of an intruder who trying to get into the system. The system is capable to processingÂ  output data from mikrotik, and it can also recognize all activities an intruder in attempt to infiltrate into the system by usingÂ  port scanner, the ssh, ftp,then do the bloking of ip address that are considered as intruder after that the system will provide a report to the administrator through webserver of the presence of an intruder who trying to get into the system.Keyboard :security system,Instrusion detection system, Mikrotik